INCREASING LEARNING OUTCOMES OF WATER CYCLE MATERIALS USING THE TEAM GAMES TOURNAMENT MODEL IN CLASS V ELEMENTARY SCHOOL STUDENTS - Tantyo Ary Yuwono (JANACITTA, 2022)
This study aims to determine the improvement of student learning outcomes through the team games tournament (tgt) model in fifth grade students of SD Negeri 01 Werdi. The type of research is Classroom Action Research (CAR). The subjects in the study were the fifth grade students of SD Negeri 01 Werdi Wonokerto Pekalongan totaling 19 students. The instruments used were interview guidelines, observation sheets, and written tests. The research was conducted in 4 stages, namely planning, implementation, observation/data collection, reflection. Data collection techniques using tests, observations and documentation. Based on the results of the daily test in the initial or pre-cycle activities, data were obtained from 19 students, 5 students with a percentage of 26.32% completed in learning, while 14 students with a percentage of 73.68% had not completed learning. After carrying out learning with the TGT model in the first cycle, the results obtained were 12 students with a percentage of 63.12% students were able to complete in learning and the remaining 7 students had not completed with a percentage of 36.88%. In the second cycle, it was found that 18 students were able to complete with a percentage of 94.73% and the remaining 1 student with a percentage of 5.26% had not completed. Based on the test data, it showed a significant increase in student learning outcomes. The results of this study prove that the use of the TGT learning model is effectively used in improving student learning outcomes.